Politician’s Dilemma: The Political Dynamics of the Pinrang Regency DPRD in Implementing Local Expenditure Efficiency Policies for the 2025 Fiscal Year - Muliadi, Andry; Ariana, Ariana; Armunanto, Andi Ali (SIGn Journal of Social Science, 2025)
The fiscal efficiency policy through Presidential Instruction Number 1 of 2025 has narrowed the regional discretionary space and triggered the politician’s dilemma for local legislative members. This study aims to analyze the manifestation of this dilemma and dissect the budget political dynamics, both at the internal factional consolidation stage and the external negotiation stage in the Pinrang Regency DPRD. This study employed a qualitative method with an intrinsic case study approach. Primary data were extracted through in-depth interviews with legislative and executive representatives, party executives, and societal elements. These data were then confronted with the literature using a source triangulation technique. The results reveal that budgetary constraints force council members to formulate electoral defense mechanisms. These mechanisms are executed by prioritizing the allocation of constituency programs to the dominant voter base areas. In the Budget Committee’s external arena, the executive bureaucracy’s defensive maneuvers utilizing technocratic compliance instruments are responded to by the legislature through compromising bargaining tactics. These tactics involve scaling down physical programs to avoid a regional budget ratification deadlock. This study concludes that the uniform budget-cutting policy has tangibly distorted the allocation of resources and transformed the council’s representative instruments into pragmatic transactional commodities. These empirical findings suggest the need for a reorientation in the formulation of an asymmetrical fiscal efficiency policy by the central government. Furthermore, the institutionalisation of a budget-priority protection mechanism at the regional level is highly necessary so that strategic development designs do not become victims of short-term factional negotiations.